The effects of recombinant human insulin‐like growth factor‐1/insulin‐like growth factor binding protein‐3 administration on lipid and carbohydrate metabolism in recreational athletes. (29th November 2020) - Guha, Nishan; Nevitt, Simon P.; Francis, Michael; Böhning, Walailuck; Böhning, Dankmar; Sönksen, Peter H.; Holt, Richard I. G.
Abstract: Objective: Previous studies suggested that recombinant human IGF‐1 (rhIGF‐1) administration affects carbohydrate and lipid metabolism in healthy people and in people with diabetes. This study aimed to determine the effects of rhIGF‐1/rhIGF binding protein‐3 (rhIGFBP‐3) administration on glucose homeostasis and lipid metabolism in healthy recreational athletes. Design and Setting: Randomized, double‐blind, placebo‐controlled rhIGF‐1/rhIGFBP‐3 administration study at Southampton General Hospital, UK. Participants: 56 recreational athletes (30 men, 26 women). Methods: Participants were randomly assigned to receive placebo, low‐dose rhIGF‐1/rhIGFBP‐3 (30 mg/day) or high‐dose rhIGF‐1/rhIGFBP‐3 (60 mg/day) for 28 days. The following variables were measured before and immediately after the treatment period: fasting lipids, glucose, insulin, C‐peptide and glycated haemoglobin. The homeostatic model assessment (HOMA‐IR) was used to estimate insulin sensitivity and indirect calorimetry to assess substrate oxidation rates. The general linear model approach was used to compare treatment group changes with the placebo group. Results: Compared with the placebo group, there was a significant reduction in fasting triglycerides in participants treated with high‐dose rhIGF‐1/rhIGFBP‐3 ( p = .030), but not in the low‐dose group ( p = .390). In women, but not in men, there were significant increases in total cholesterol ( p = .003), HDL cholesterol ( p = .001) and LDL cholesterol ( p = .008). These lipid changes were associated with reduced fasting insulin ( p = .010), C‐peptide ( p = .001) and HOMA‐IR ( p = .018) in women and reduced C‐peptide ( p = .046) in men. Conclusions: rhIGF‐1/rhIGFBP‐3 administration for 28 days reduced insulin concentration, improved insulin sensitivity and had significant effects on lipid profile including decreased fasting triglycerides.